Quality of life after low-dose rate-brachytherapy for prostate carcinoma: long-term results and literature review on QLQ-C30 and QLQ-PR25 results in published brachytherapy series - Bürgy, Daniel; Schneiberg, Vincent Thomas; Schäfer, Jörg; Welzel, Grit; Wenz, Frederik (Health and quality of life outcomes, 2018)
Background: Patient-reported health-related quality of life (HRQOL) differs between treatment options for prostate carcinoma. Long-term HRQOL data in brachytherapy series are scarce. Therefore, we analyzed prostate-specific and general HRQOL in patients treated with brachytherapy for prostate carcinoma after long-term follow-up. Methods: Two hundred ninety-six patients with prostate carcinoma were treated with brachytherapy (01/1998-11/2003). General and prostate-specific HRQOL were measured using EORTC-QLQ-C30 and EORTC-QLQ-PR25, respectively. Patients were asked to complete the questionnaires after a median follow-up of 141 (119-181) months. QLQ-C30 results were compared to the German reference population. QLQ-PR25 results were compared to an earlier follow-up after a median of 51 months (no published QLQ-PR25 reference population for comparison). Additionally, a literature review on HRQOL data in brachytherapy series was performed. Results: One hundred six (35.8%) patients were lost to follow-up, 70 (23.6%) had died. 120 (40.5%) patients were contacted. 80 questionnaires were returned (27% of the original cohort; 91% of alive patients were ≥70 years). Sexual activity declined over time (mean scores: 40.5 vs. 45.5; p = 0.006), hormonal treatment-related symptoms, problems associated with incontinence aids, and burden of obstructive urinary symptoms did not differ significantly compared to the 51-month follow-up. General HRQOL was numerically better in our cohort as compared to the German reference population (> 16% relative difference for both age strata; < 70 and ≥70 years). Conclusions: Our results indicate that symptom-burden after long-term follow-up and associated prostate-specific HRQOL remains relatively stable from 51 to 141 months. General HRQOL in surviving patients was numerically better compared to the reference population.
Gesehen am 02.09.2019